Research hotspots and nursing inspiration in research of older adults with subjective cognitive decline from 2003 to 2023: A bibliometric analysis - Xiaotong Ding; Jiyuan Shi; Qing Wang; Hongli Chen; Xiuxiu Shi; Zheng Li (Elsevier, 2024)
Objectives: There has been a significant increase in subjective cognitive decline (SCD) studies in older adults over the years. A bibliometric analysis was conducted to demonstrate the current hotspots and emerging trends in SCD research in older adults and provide references for further research in this field. Methods: The study conducted a bibliometric analysis based on co-citation analysis. From the Web of Science Core Collection database, this study obtained 1,436 manuscripts regarding SCD in older adults published from 2003 to 2023. Software CiteSpace was used to analyse the results for countries, institutions, authors, journals, keywords, top-cited papers, and burst citations scientifically and intuitively. Results: Our result showed an overall upward trend in the volume of publications on SCD in the elderly population, suggesting that the study of SCD in older adults has attracted the attention of researchers. The United States dominates this research field, followed by China and France. The top three institutions were the University of California System, Institut National de la Sante et de la Recherche Medicale (Inserm), and UDICE-French Research Universities. Frank Jessen, Han Ying, and Kathryn Ellis were the top three researchers. The top three cited journals were Neurology, Alzheimers & Dementia, and Journal of Alzheimer's Disease. The keywords clustering were "depression", "functional connectivity", "cognitive reserve", "cognitive function", "physical activity", "recommendations", "dementia prevention", " behavioral disorders", "primary care", "early diagnosis", and "community-based study". Keywords with the highest citation bursts include "physical activity", "framework", "preclinical Alzheimer's disease", "future dementia", and "late life depression". Conclusions: Parallel to the growth trend, the range of research scopes and topics is expanding steadily, focusing on early screening and prevention, negative emotion, and symptom management, broadening researchers' perspectives, which can provide reference and guidance for nursing researchers to conduct research.